Genetic Analysis Of Grain Quality Characteristics Of Two Line Rice Hybrids - L. Mahalingam and N. Nadarajan (Electronic Journal of Plant Breeding, 2010)
The experiment was laid out at Agricultural College and Research Institute Madurai, Tamil Nadu, India and the materials forthis study consisted of three TGMS lines viz., TS 29, TS 6 and 11 testers viz.,ADT 39, ADT41,Pusa Basmati 1, Basmati 370,Improved White Ponni, AD 98028, GEB 24, ADT 43, ADT 45, Taroari Basmati and Jeeraga samba. Crossing was doneaccording to clipping and churning method in L x T fashion. The 33 hybrids obtained by crossing three lines and eleventesters were raised in randomized block design with two replications during 2004-2005. The parents were also raised insimilar design in an adjacent plot with two replications as suggested by Arunachalam (1974). Observations were made onKL, KB, KLAC, LER, VER, ASV, GC and AC. Based on the nature of combining ability inferred from line x tester analysis,three cross combinations viz., TS29/ADT41, TS29/Pusa Basmati 1 and TS29 / Basmati 370 were selected for generationmean analysis study. The scaling tests indicated the presence of epitasis for all the characters and therefore six parametersmode was followed to estimate the various gene action. In TS29/Basmati 370 cross combination all the three scales arepositively significant. The mean effect m was significantly positive and greater than all other effects in all the three crossesfor kernel breadth, kernel length after cooking, volume expansion ratio, alkali spreading value, gel consistency and amylosecontent. The additive x dominance effect (j) was positive and significant for kernel length after cooking, linear elongationratio, gel consistency and amylose content in the crosses TS29/ADT41, TS29/Pusa Basmati 1 and TS29/Basmati 370.Ingeneral, both additive and non-additive gene effects appear to all eight characters studied. Therefore, improvement of thesetraits appears to beset with difficulties as simple selection techniques will not be able to fix superior lines in the earlysegregating generations. Postponement of selection of superior lines to later generations in pedigree breeding will beeffective.